Determinants of Traditional Birth Attendants Compliance to Existing Legal Frameworks against Female Genital Mutilation/ Cutting in Garissa County, Kenya - Songok, Sosten; Mugo, Judy; Thigiti, Joseph (Global Journal of Health Sciences, 2025)
Purpose: The study sought to establish the determinants of traditional birth attendants’ compliances to existing legal frameworks against female genital mutilation/ cutting in Garissa County, Kenya. The study intended to answer complex interplay of cultural, religious, and social factors influencing traditional birth attendants' compliance with legal frameworks against FGM/C. Methodology: Study adopted cross sectional study design. Mixed methods approach (Survey and KIIs) was used to collect data. Targeted TBAs, law enforcers and opinion leaders residing in Dadaab Sub- County. Semi-structured questionnaires were used to collect quantitative data while key informant interview guide was used to collect qualitative data. Quantitative data collected was entered into Epidata (version 3.1) database then exported to R (version 3.6.4) for analysis while qualitative data were thematically analysed. 261 participants were recruited, with 86.21% being compliant to existing law against FGM/C. Findings: The independent predictors for compliance to existing legal frameworks against FGM/C in this study were marital status of the active TBAs: married (AOR=7.78, 95% CI=2.4544-24.6443, p<0.001) and widowed (AOR=4.76, 95% CI=1.2063-18.8181, p=0.0259); Education level of the active TBAs: primary education (AOR=5.80, 95% CI=1.3887-24.2616, p=0.016); Required ages for girls/women before circumcision being 5-11 years (AOR=7.91, 95%, CI=2.73-22.95, p<0.001); Mothers accompanying girls/women to circumcision (AOR=7.02, 95% CI=2.0899-23.6125, p=0.0016); Religious background of girls/women to be circumcised (AOR=2.94, 95% CI=1.1688-7.4096, p=0.022); active TBAs who asserted that FGM/C was still deemed necessary in their community (AOR=0.11, 95% CI=0.0146-0.8844, p=0.0378); active TBAs who identified FGM/C Type I as the most predominant in their community (AOR=0.10, 95% CI=0.0261-0.3673, p<0.001); FGM/C being practiced for traditional purposes traditional (AOR=9.86, 95% CI=1.8419-52.7653, p=0.0075); Advocacy through religious approaches on the abandonment of FGM/C (AOR=5.90, 95% CI=2.173-16.0309, p<0.001); active TBAs cognizant of the punishments imposed on perpetrators and accomplices of FGM/C (AOR=3.11, 95% CI=1.279-7.5576, p=0.0123); active TBAs aware of the laws/legislations prohibiting FGM/C in Kenya (AOR=3.06, 95% CI=1.3759-6.7912, p=0.0061); Active TBAs supporting for the education of TBAs on existing anti-FGM/C laws (AOR=4.64, 95% CI=1.7885-12.0514, p=0.0016); active TBAs aware of someone in the community who had reported FGM/C as a crime (AOR=2.71, 95% CI=1.2296-5.9762, p=0.0134). Unique Contribution to Theory, Practice and Policy: Information from the study will influence policy formulation and complement existing literature.